(untitled) (Bangladesh Journal of Otorhinolaryngology, 2014)
Objectives: To determine the pattern of clinical presentation of hypopharyngeal carcinoma and pattern of metastases. Methods: This was a cross sectional study with 60 patients. Study was carried out in the Department of Otolaryngology and Head Neck Surgery, Bangabandhu Sheikh Mujib Medical University, Dhaka Medical College Hospital and Mitford Hospital during the period of July 2005 to June 2007. This diagnosis was made by detailed history clinical examination and relevant investigation. Analyzed data and presented by various tables, graphs and figures. Result: In this study majority of the patients were within 51-60 years, male female ratio was 7.5:1, majority was smoker (91.66%), 58% patients had habit of tea, 88.32% of the patients chewed betel, Majority of the patients (81.16%) had presented with progressive dysphagia 76.66% and hoarseness of voice (60%), There was neck swelling in 53.3% and haemoptysis in 25% of patients. 63.33% patients had ulcerative lesion, 40% normal laryngeal movements, 63.33% were adequate airway, 65% patient had cervical lympadenopathy. Primary lesion was 75% in pyriform fossa, 20% in post cricoid region and 5% in posterior pharyngeal wall. 46.66% were T3 stage, 53.33% N1 and 48.71% were level IV nodal involvement. Conclusion: Hypophayngeal carcinoma usually presents in advanced state. DOI: http://dx.doi.org/10.3329/bjo.v19i2.17630 Bangladesh J Otorhinolaryngol 2013; 19(2): 87-93